Contemporary islamic theology in Iran - Rexhepi, Abdulla (Edinost in dialog, 2024)
After the Iranian Revolution's success in 1979, authority transferred to Islamist factions, swiftly establishing a political framework predominantly grounded in the Shiite Islamic legal principles of the Twelve Imams. The emerging political structure and its Islamic proponents encountered unprecedented circumstances and challenges necessitating modern perspectives and interpretations. Nonetheless, traditional Shiite epistemological frameworks proved inadequate in providing scientific methods to address these issues. Consequently, a group of scholars among Muslim clerics and intellectuals surfaced, engaging not only in classical Islamic theological studies but also in exploring contemporary Western knowledge. This endeavour introduced a new outlook into Iran's theological discussions. This article aims to outline the emergence of a theological movement in Iran by examining the contemporary concepts deliberated by scholars like Mohammad M. Shabestari, Mustafa Malekian, and Mohsen Kadivar. Their Islamic hermeneutical initiatives have significantly contested conventional Shiite theology, despite its continuing dominance in the Islamic religious spheres within the nation. The article posits that the fresh theological ideas and concepts introduced by these three Iranian scholars have wielded substantial influence within emerging intellectual, academic, and university circles in Iran. Moreover, these ideas have extended beyond the confines of Islamic theological spheres, promoting a conciliatory atmosphere between Iranian Islamists and modernists.
Keywords: contemporary islamic theology; Iran; Islamic Shiite orthodoxy; islamska šiitska ortodoksija; Kadivar, Mohsen; Malekian, Mostafa; Shabestari, Mohammad Mojtahed; sodobna islamska teologija